Is It Safe to Perform an Early Arthroscopy After a Traumatic Hip Dislocation With an Associated Pelvic Ring Injury? Report of Our Technique - Geada, N (2018)
Hip arthroscopy is useful in the treatment of several intra-articular pathologies, however, its use in high-energy hip and pelvis injuries raises concerns about fluid extravasion and stability of the pelvic ring. We present our arthroscopic surgical technique (initial access to the peripheral compartment) to remove intra-articular loose bodies and treat associated lesions, as well as our concerns with the technique, in case of a traumatic hip dislocation associated with a contralateral pelvic ring injury.